Паводки та управління ними в регіоні Українських Карпат і прилеглих територій - Приходько, М.М. (Український географічний журнал, 2011)
Рассмотрены природные и антропогенные факторы формирования паводков в регионе Украинских Карпат и
прилегающих территорий. Определено, что паводки здесь возникают главным образом вследствие интенсивных
осадков, сложных геоморфологических условий и значительного снижения водоаккумулирующей емкости территории
в связи с сокращением в 2-5 раз площади лесов. Обоснована стратегия управления паводком (паводковым риском) в
бассейнах рек, которая включает систему взаимоувязанных противопаводковых мероприятий. The natural and anthropogenic factors of flood formation in Ukrainian Carpathians and surrounding territories are discussed
in the article. It is proved, that floods on this territory are caused mainly by intensive precipitation, complex geomorphologic
conditions and substantial declining of water storage capacity of the territory as a result of reduction of forest areas in 2-5
times. There has been substantiated the strategy of flood management (flood risk management) in the basins including the
system of interconnected anti-flood measures.